"Comparación de parámetros físico-químico de huevos criollo y comerciales en el cantón Mocache" - Mora Erazo, Jorge Alfredo (2018)
Many chemical and nutritional studies have shown that the components of the egg and the consumption of these are necessary for human nutrition but that these are disadvantaged under the presence of many factors such as microorganisms that alter their nutritional quality. Over the years, commercial eggs have been taking over the years in the market both globally and nationally, thus achieving that the field eggs or Creole chickens are little commercialized at present. The present study was carried out with the objective of comparing the physical and chemical components in Creole eggs in 4 associations; (T1) La Mariana, (T2) United to Overcome, (T3) Joy of the field and (T4) Cañaveral, and while the (T5) the commercial egg was used as a witness. A reference sample of each association was collected, 40 eggs of Creole hens per treatment, in total 160 Creole eggs were collected, and the control was collected 40 commercial eggs, was used as a DCA design with 5 treatments and 4 repetitions (10 eggs per repetition), all the physical parameters of both Creole and commercial eggs were subjected to ANOVA, resulting in commercial eggs obtaining a difference (P˂0.05) from Creole eggs. For the bromatological analysis, moisture ash proteins were analyzed in which they were extracted by separate, clear yolks and complete eggs (yolks + clear) this with the purpose of knowing their chemical content, where it was demonstrated that the protein content was higher in the Creole eggs in both yolks and fulls were superior to commercial ones. For the determination of quality and nutrition, the microorganism was counted; mesophilic bacteria, B. CF coleiformes and fungi. In order to know the degree of tasting, a hedonic scale was carried out and the selection of judges dictated an ultimatum to know the value of the components to be evaluated such as smell taste, texture and color, resulting in the final result that creole eggs have more acceptance as to its smell and flavor as to the creole eggs. Keywords: protein, laboratory, creole eggs, commercial eggs